Perilaku Pemustaka dalam Memperlakukan Koleksi Perpustakaan: Studi Kasus di Perpustakaan Universitas Indonesia - Suhaila, Suhaila; Rachman, Yeni Budi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2017)
This study discusses the user attitudes in handling library materials. The study was conducted at the library of University of Indonesia. This research uses qualitative approach with case study. The data was collected by conducting observation, interview, and document analysis. The finding shows there are some of book mutilation and vandalism activities caused by users. This study suggests that the library needs to conduct a user preservation education program to prevent vandalism.